PENGARUH FORMULASI MIKROENKAPSULASI EKSTRAK KULIT MANGGIS TERHADAP KADAR AIR DAN SEBARAN JAMUR PADA LAMA PENYIMPANAN YANG BERBEDA - Andri Kusmayadi (AGROINTEK, 2021)
The purpose of this study was to examine the effect of formulation on microencapsulation products of mangosteen peel extract encapsulated by maltodextrin from Arenga starch on water content and fungus distribution. The treatments tested consisted of: M1 (70% MPE: 30% maltodextrin/MDX), M2 (60% MPE: 40% MDX), M3 (50% MPE: 50% MDX), M4 (40% MPE: 60% MDX), M5 (30% MPE: 70% MDX), and M6 (100% mangosteen peel extract/MPE). Each treatment was observed for 0, 2, 4, 6, and 8 weeks. The results showed that the microencapsulation treatment of mangosteen peel extract with maltodextrin (M1 – M5) had a significant effect (P0.05) on water content and fungus distribution. The water content of the sample starts to increase in the second week and increases with increasing shelf life. The fungal distribution parameters showed the formation of colonies and product damage in the fourth week and continued to increase until the eighth week. This study shows that the microencapsulation treatment (M1 - M5) is able to protect the material from environmental influences and can extend the shelf life of the material rather than the control treatment (M6). The M4 treatment containing 40% mangosteen peel extract and 60% maltodextrin showed the best results on the water content and fungul distribution.